2019
DOI: 10.25225/fozo.040.2019
|View full text |Cite
|
Sign up to set email alerts
|

Space use, habitat selection and daily activity of water voles Arvicola amphibius co-occurring with the invasive American mink Neovison vison

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…The obtained results suggest that, in the study area, mink odour was recognized by water voles as a threat and that, three decades after the establishment of the mink population, voles did not display prey naivety towards the non-native predator. A study of water vole activity conducted previously at the midfield ponds near Lake Łuknajno revealed that water voles avoided terrestrial habitats and preferred to inhabit pond littoral zones (Brzeziński, Jedlikowski, & Komar, 2019). In our experiment, these habitat preferences of water voles were further confirmed by the significantly higher trappability in traps placed on the rafts located in deeper water and more distant to the pond shoreline.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…The obtained results suggest that, in the study area, mink odour was recognized by water voles as a threat and that, three decades after the establishment of the mink population, voles did not display prey naivety towards the non-native predator. A study of water vole activity conducted previously at the midfield ponds near Lake Łuknajno revealed that water voles avoided terrestrial habitats and preferred to inhabit pond littoral zones (Brzeziński, Jedlikowski, & Komar, 2019). In our experiment, these habitat preferences of water voles were further confirmed by the significantly higher trappability in traps placed on the rafts located in deeper water and more distant to the pond shoreline.…”
Section: Discussionsupporting
confidence: 79%
“…Similarly, we did not record any changes in the pattern of vole circadian activity. In the study area, water voles display nocturnal activity (Brzeziński et al, ), and during the experiment, they were still mostly nocturnal, both in the areas with and without deployed mink faeces.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The high frequency of remains of two vole species and moles in pellets suggests that these species are preyed upon in large numbers by herons feeding along shorelines or even on land, and that voles could be important primary vectors for plant seeds. Both vole species are herbivores that feed on plant material and seeds (Brzezinski et al., 2019; Lee & Houston, 1993). Even if seeds ingested by voles do not normally survive passage through the entire mammalian gut, they could still be in the mammalian foregut at the time of predation, or be carried in their fur (Cook, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…At times when an observer saw a chipmunk without disturbing it, the observer recorded the exact location of that chipmunk with a GPS unit after the chipmunk had left the vicinity. To maintain temporal independence for each chipmunk, we waited ≥ 1 h before obtaining a subsequent location ( Brzeziński et al 2019 ).…”
Section: Methodsmentioning
confidence: 99%